The Women’s Role in Supporting Family Businesses - Tobak, Júia (International Journal of Engineering and Management Sciences, 2018)
The women’s role in supporting family businesses is important. As a wife, mother and chief trust officer the female family members effect on the operation of the family business directly or indirectly. A questionnaire was prepared for better understanding how the female family members can contribute to the family business. The results include information about successor related decisions and about generational changes. There are some information about change of the different woman’s roles within family and business.